FUTURE TEACHER’S EMOTIONAL INTELLIGENCE IN SPIRITUALLY-MORAL DIMENSION - Rakityanska, Ludmila (The Modern Higher Education Review, 2020)
The study focuses on the problem of a new generation teacher education and training in epoch of technogenic civilization, which is characterized by further scientific and technological progress, on one hand, and, by spiritual degradation in society caused by the material benefits for society, on other hand. Moreover, “psychological” crisis, connected with the general “mental illness” of the society is becoming global. “Bringing mind to emotions” is the leading idea of the theory of emotional intelligence of American scientists, who see it as a panacea in the contemporary society. The theory of emotional intelligence, which is widely recognized in the world, is attracting the attention of Ukrainian scientists, in particular, in higher education. Ukrainian scientists interpret the emotional intelligence of the teacher as a personal and professional quality that provides professional acmeological growth, productive, professional, humanistic oriented activity, effective interpersonal communication, stress-protective function. It is concluded, that these criteria should guide the professional training and education of new generation teachers.